Gut microbiome, metabolome and alopecia areata - Liu, Zhiyu; Liu, Xiaoyan (Frontiers in Microbiology, 2023)
Alopecia areata (AA) is a type of dermatological disease characterized by rapid and non-scarring hair loss of the scalp or body skin that may be related to genetic, immunological and physiological factors.It is now believed that AA is associated with oxidative stress, autoimmune disease, neuropsychological factors, pathogens, immune checkpoint inhibitors and microecological imbalance under the premise of host genetic susceptibility. In recent years, studies have revealed the significant role of the gut microbiome or metabolome in many aspects of human health. Diverse studies have revealed that the gut microbiome and metabolome have an important influence on skin conditions. This review highlights the relationship between AA and the gut microbiome or metabolome to provide novel directions for the prevention, clinical diagnosis and treatment of AA.